A fathers' group in NICU: Recognising and responding to paternal stress, utilising peer support. Issue 6 (December 2017) - Thomson-Salo, Frances; Kuschel, Carl A.; Kamlin, Omar F.; Cuzzilla, Rocco
Abstract: This clinical communication aims to describe successful program development of a weekly group for fathers of infants in the 60-bed tertiary Newborn Intensive Care unit of the Royal Women's Hospital, Melbourne, Australia, established in 2013 to address considerable paternal stress in the perinatal period. The Group's structure and functioning is described: it is open to all fathers with an infant in the unit and co-facilitated by neonatologists and an embedded psychologist who is an infant mental health clinician. Five themes are described including the predominant theme of the traumatic aspects of the birth and subsequent difficulties in parenting and bonding associated with in-patient admission. Most fathers give immediate positive feedback about the peer support gained from this Group, as do other clinical staff.